(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This in the article youth in mind forming religious views, their modern socio-cultural processes under the influence change and this of processes society in development place analysis will be done. Also, globalization, information of the place expansion, religious-enlightenment to sources entrance easier such as of factors youth worldview and belief to the formation shown positive and negative effects seeing was published. In the study socio-philosophical approach through youth in faith changes essence open is given and them deep of learning necessity based on given.